Metagenomic indications of potential pathogen-associated and antibiotic resistance risks following UV–chlorine disinfection in sprout production - Yufei Wei; Lin Zhu; Xiangfu Jin; Huangli Yao; Shanshan He; Pu Feng; Feihong Yu; Yulu Xiang; Zhiheng Li; Shanying He (Environmental Pollution, 2026)

Physics-informed model predictive control for active heave compensation of electrical winches - Ruhua Zhang; Wenhua Li; Shanying Lin; Gen Li; Haoran Ye; Xingjian Lou (Ocean Engineering, 2026)

Study on sliding wear mechanism and performance degradation of polyurethane-coated HMPE ropes in sheave systems for deep-sea winch - Yiqun Lin; Wenhua Li; Gen Li; Shanying Lin; Haoran Ye; Hangyu Li (Ocean Engineering, 2026)

Vortex-induced vibration of subsea rigid jumpers conveying gas–liquid two-phase flow - Guangzhao Li; Wenhua Li; Shanying Lin; Haoran Ye; Gen Li (Ocean Engineering, 2026)

Nonlinear modeling and dynamic analysis of wireline riser tensioners for deep-sea mining risers - Yan Li; Wenhua Li; Baoyun Qi; Haoran Ye; Shanying Lin; Gen Li (Ocean Engineering, 2026)

Multi-Objective Optimization Design of Cylindrical FPSO Mooring System Based on KAN Surrogate Model and NSGA-III Algorithm - Wenhua Li; Mingshuai Yu; Huoping Wang; Haoran Ye; Liuzhong Cao; Shanying Lin (Journal of Marine Science and Engineering, 2026)
Cylindrical floating production storage and offloading (FPSO) units are advancing into deeper waters. Overcoming the severe challenges posed by complex deepwater environments requires the design of mooring systems that balance economic efficiency and mooring performance. This paper proposes an innovative optimization method for cylindrical FPSO mooring systems, combining the Kolmogorov–Arnold Network (KAN) with the Non-dominated Sorting Genetic Algorithm III (NSGA-III). Configuration samples are generated within predefined design variable ranges using Latin Hypercube Sampling (LHS), followed by time-domain global response simulations using OrcaFlex (version 11.3) software. A KAN surrogate model is constructed to predict the dynamic responses of the mooring system. Finally, the NSGA-III algorithm is employed for multi-objective optimization to obtain the Pareto optimal set, aiming to minimize mooring costs, maximum tension, fatigue damage, and platform offset. The results demonstrate that, compared to traditional optimization methods, the combination of KAN and NSGA-III exhibits superior prediction accuracy and generalization capabilities. The optimized configurations significantly outperform the original design in both mooring performance and economic costs. Specifically, the most economical scheme reduces mooring costs by 20.73%, the minimum tension scheme decreases mooring line tension by 46.75%, and the minimum displacement scheme reduces platform offset by 30.88%.

Study on the characteristics and prediction model of gas-liquid two-phase slug flow in subsea jumper - Wenrui Song; Wenhua Li; Shanying Lin; Haoran Ye; Gen Li (Ocean Engineering, 2026)

Experimental and numerical research on thermal characteristics and ampacity of multi-layer wound non-metallic armoured optoelectronic cable winch system in Oceanographic Research Vessel - Wenhua Li; Yujie Zhang; Shanying Lin; Gen Li; Weiwei Shen (Ocean Engineering, 2026)

Dynamic response optimisation of active heave compensation systems for electrical winches - Ruhua Zhang; Wenhua Li; Shanying Lin; Gen Li; Ping Zhang; Shijie Xu (Ocean Engineering, 2026)

Flow-induced vibration suppression of a square cylinder with Y-shaped jet configuration: Inspired by fish gill structures - Yiqun Lin; Wenhua Li; Gen Li; Fenghui Han; Shanying Lin; Haoran Ye (Ocean Engineering, 2026)

Flow-induced vibration and stress prediction of subsea M-shaped jumpers under multiphase flow - Guangzhao Li; Wenhua Li; Shanying Lin; Haoran Ye; Gen Li (Ocean Engineering, 2025)

Quantitative evaluation method for the winding package deformation of non-metallic armored CTD cable on the multi-layer winch - Shanying Lin; Zehua Li; Wenhua Li; Haoran Ye; Lei Hong; Fei Wang (Ocean Engineering, 2025)

Experimental and Numerical Study on the Temperature Rise Characteristics of Multi-Layer Winding Non-Metallic Armored Optoelectronic Cable - Shanying Lin; Xihong Kuang; Yujie Zhang; Gen Li; Wenhua Li; Weiwei Shen (Journal of Marine Science and Engineering, 2025)
The non-metallic armored optoelectronic cable (NAOC) serves as a critical component in deep-sea scientific winch systems. Due to its low density and excellent corrosion resistance, it has been widely adopted in marine exploration. However, as the operational water depth increases, the NAOC is subjected to multi-layer winding on the drum, resulting in a cumulative temperature rise that can severely impair insulation performance and compromise the safety of deep-sea operations. To address this issue, this paper conducts temperature rise experiments on NAOCs using a distributed temperature sensing test rig to investigate the effects of the number of winding layers and current amplitude on their temperature rise characteristics. Based on the experimental results, an electromagnetic thermal multi-physics field coupling simulation model is established to further examine the influence of these factors on the maximum operation time of the NAOC. Finally, a multi-variable predictive model for maximum operation time is developed, incorporating current amplitude, the number of winding layers, and ambient temperature, with a fitting accuracy of 97.92%. This research provides theoretical and technical support for ensuring the safety of deep-sea scientific operations and improving the reliability of deep-sea equipment.

An adaptive control method of non-metallic armoured Optical-electrical cable winch system in Oceanographic Research Vessel based on three-dimensional laser scanning point cloud - Haoran Ye; Hongjie Guo; Wenhua Li; Shanying Lin; Gen Li; Lei Hong (Ocean Engineering, 2025)

Experimental and numerical investigation of flow pattern evolution and flow-induced vibrations in an M-shaped subsea jumper under gas-liquid two-phase flow conditions - Wenrui Song; Wenhua Li; Shanying Lin; Haoran Ye; Gen Li (Ocean Engineering, 2025)

Real-Time Fault Diagnosis of Mooring Chain Jack Hydraulic System Based on Multi-Scale Feature Fusion Under Diverse Operating Conditions - Yujia Liu; Wenhua Li; Haoran Ye; Shanying Lin; Lei Hong (Journal of Marine Science and Engineering, 2025)
The condition monitoring of mooring equipment is an important engineering reliability issue during the operation of a floating production storage and offloading unit (FPSO). The chain jack (CJ) is the key equipment for powering the mooring chain in a spread mooring system. Under complex and dynamic marine operating conditions, different severity faults in the CJ hydraulic system display distinct time-scale characteristics. Hence, this paper proposes a real-time fault diagnosis method of the CJ hydraulic system based on multi-scale feature fusion. Firstly, the model incorporates a convolutional neural network (CNN) layer to extract localized spatial features from multivariate time-series data, effectively identifying fault patterns over the associated short intervals. Subsequently, the bidirectional long short-term memory (BiLSTM) layer is introduced to construct a dynamic temporal model to comprehensively capture the evolution of the fault severity. Finally, a multi-scale global attention mechanism (GAM) emphasizes persistent fault behaviors across time scales, dynamically prioritizing relevant features to improve diagnostic accuracy and model interpretability. The study results indicate that the proposed model’s accuracy improves by 7.36% over the CNN-GAM for 11 failure modes, up to 99.34%. This study contributes to the safe operation of an FPSO by guiding monitoring CJ operations under different load conditions.

Active heave compensation of marine winch based on hybrid neural network prediction and sliding mode controller with a high-gain observer - Wenhua Li; Chuanchao Wu; Shanying Lin; Gen Li; Ping Zhang (Ocean Engineering, 2025)

Experimental investigation and numerical study of multiphase flow characteristics in the M-shaped jumper with different bend curvature radii - Shanying Lin; Yiwen Liu; Wenhua Li; Gen Li; Wenrui Song (Ocean Engineering, 2025)

Performances and mechanisms of catalytic ozonation for paint wastewater via catalysts of Fe-Mn deposited within graphitized beads of γ-Al2O3 - Mei Dai; Chunping Yang; Liusiyu Yang; Yan Lin; Shanying He; Xiang Li; Qiuya Niu; Shaohua Wu (Journal of Cleaner Production, 2025)

Experimental and simulation study of pounding tuned mass damper on jumper flow induced vibration - Shanying Lin; Shengyan Pan; Wenhua Li; Haoran Ye; Guangzhao Li (Ocean Engineering, 2025)

Air-sea CO2 exchange in the western Pacific influenced by monsoon and giant diatom (Ethmodiscus rex) blooms during the last deglaciation - Huaineng Tang; Haoran Ye; Wenqing Yang; Yikang Huang; Tiantai Sun; Yangyuan Ge; Hongxin Zhang; Yuqing Sun; Shanying Lin; Zhonghui Liu; Wenhua Li; Zhouqing Xie (Journal of Asian Earth Sciences, 2024)

Dynamic Response Assessment of Floating Offshore Wind Turbine Mooring Systems with Different In-Line Tensioner Configurations Based on Fully Coupled Load Calculations - Wenhua Li; Guanlin Du; Shanying Lin; Zhenju Chuang; Fei Wang (Journal of Marine Science and Engineering, 2024)
In-line tensioning technology has significantly reduced the cost barriers that previously hindered the expansion of the floating offshore wind industry. However, assessing the impact of in-line tensioners on the dynamic response of floating offshore wind turbines (FOWTs) lacks effectiveness, and the relevant mooring configuration specifications are not complete. Thus, a fully coupled calculation method is introduced in this paper to solve the relevant issues in mooring systems with in-line tensioners using a classic spar platform model. Three distinct design scenarios were selected to study the variation in mooring configurations of in-line tensioners along different mooring lines and at varied positions within each line. The potential occurrence of reverse tension phenomena was deliberated and assessed. We identified the varying tension patterns at the fairlead and in-line tensioner locations in mooring systems with in-line tensioners, and the influence of such variations on platform dynamics. The findings also demonstrate that the appropriate configuration of in-line tensioners should be selected to avoid the risk of reverse tension. This research has potential to contribute to the security and economy of the deployment of this emerging in-line mooring method.

Role of polarized and interfacial built-in electric fields in photocatalysts for enhanced photocatalytic performance - Caiyu Luo; Chunping Yang; Jun Xie; Xiang Li; Yan Lin; Shehua Tong; Shanying He (Chemical Engineering Journal, 2024)

Dynamic Response Analysis of a Subsea Rigid M-Shaped Jumper under Combined Internal and External Flows - Guangzhao Li; Wenhua Li; Shanying Lin; Fenghui Han; Xingkun Zhou (Journal of Marine Science and Engineering, 2024)
To analyze the dynamic response of a rigid M-shaped jumper subjected to combined internal and external flows, a one-way coupled fluid–structure interaction process is applied. First, CFD simulations are conducted separately for the internal and external fluid domains. The pressure histories on the inner and outer walls are exported and loaded into the finite element model using inverse distance interpolation. Then, FEA is performed to determine the dynamic response, followed by a fatigue assessment based on the obtained stress data. The displacement, acceleration, and stress distribution along the M-shaped jumper are obtained. External flow velocity dominates the displacements, while internal flow velocity dominates the vibrations and stresses. The structural response to the combined effect of internal and external flows, plus the response to gravity alone, equals the sum of the structural responses to internal flow alone and external flow alone. Fatigue damage is calculated for the bend exhibiting the most intense vibration and higher stress levels, and the locations with significant damage correspond to areas with high maximum von Mises stress. This paper aims to evaluate multiple flow fields acting simultaneously on subsea pipelines and to identify the main factors that provide valuable information for their design, monitoring, and maintenance.

East Asian Winter Monsoon and enhanced stratification in the western Pacific promoted giant marine diatom (Ethmodiscus rex) blooms during the last deglaciation - Huaineng Tang; Haoran Ye; Wenqing Yang; Yikang Huang; Tiantai Sun; Yangyuan Ge; Hongxin Zhang; Yuqing Sun; Shanying Lin; Zhonghui Liu; Wenhua Li; Zhouqing Xie (Quaternary Science Reviews, 2024)

Numerical Study on Electromagnetic Thermal Performance of Non-Metallic Armoured Optoelectronic Cable Winch System - Wenhua Li; Huaizhao Wu; Shanying Lin; Weiwei Shen; Qingtao Lv (Journal of Marine Science and Engineering, 2024)
Non-metallic armoured optoelectronic cable winch systems (NAOCWSs) play critical roles in facilitating signal transmission and powering subsea equipment. Due to the varying depths in these applications, deploying the entire cable length is unnecessary. However, the portion of the cable that remains coiled around the winch can generate an electromagnetic field, which may interfere with signal transmission and induce electromagnetic heating. This can lead to elevated temperatures within the system, affecting the cable’s lifespan. Consequently, this study examines the distributions of magnetic and temperature fields within the NAOCWS with different currents (10–30 A) and numbers of winding layers (1–10). Findings indicate that the magnetic flux density (MFD) changes periodically, and the period is closely related to the distance between the cables. At the centre of the cable, the flux density is minimum. Temperature distribution correlates with both current amplitude and the number of winding layers, where an increase in either parameter amplifies the temperature variance between the edge and intermediate cables within the same layer. The current does not affect the internal temperature distribution pattern. With the number of winding layers determined, the layer where the highest temperature of the system is located is well defined and does not vary with current.

Experimental research and numerical study of leakage influence on the internal two-phase flow of subsea jumper - Shanying Lin; Xuming Yang; Shengnan Liu; Muk Chen Ong; Wenhua Li (Ocean Engineering, 2024)

Flow pattern evolution and flow-induced vibration response in multiphase flow within an M-shaped subsea jumper - Wenrui Song; Wenhua Li; Shanying Lin; Xingkun Zhou; Fenghui Han (Ocean Engineering, 2024)

Load Assessment Method for Multi-Layer Oceanographic Winch with Synthetic Fibre Ropes Based on Non-Rotation Symmetric Cylindrical Model - Haoran Ye; Wenhua Li; Shanying Lin; Qingtao Lv; Dinghua Zhang (Journal of Marine Science and Engineering, 2024)
Offshore winches are crucial in marine engineering, particularly in marine scientific research and deep-sea exploration. The use of fibre ropes presents significant opportunities for the weight reduction of winches as a consequence of the low length–strength ratio and characteristics of corrosion resistance. Nonetheless, a challenge arises in underestimating the stress load levels in load assessments of multi-layer winch systems using synthetic fibre ropes. Traditional computational methods reliant on symmetrically rotational models fall short in accurately predicting and assessing practical applications. This paper introduces a finite element analysis model based on a non-rotationally symmetric approach with four surfaces subjected to various radial pressure on account of the deformation of the fibre ropes. In the design model, sixteen stress detection paths have been incorporated to identify and confirm non-linear stresses. The outcomes of the finite element simulations have been compared with experimental results with two synthetic fibre ropes, each with distinct deformation characteristics utilised. The findings demonstrate that the application of the model aligns well with experimental results, showcasing its relevance and practical value in real-world scenarios. Precise theoretical calculations and experimental validation are pivotal to ensuring that equipment reliability and safety are maintained alongside the pursuit of light-weighting.

Functional biochar in enhanced anaerobic digestion: Synthesis, performances, and mechanisms - Wenkai Nie; Shanying He; Yan Lin; Jay J. Cheng; Chunping Yang (Science of The Total Environment, 2024)

Singlet oxygen: Properties, generation, detection, and environmental applications - Yue Wang; Yan Lin; Shanying He; Shaohua Wu; Chunping Yang (Journal of Hazardous Materials, 2024)

Prediction and control strategy based on optimized active disturbance rejection control for AHC system - Wenhua Li; Chang Xu; Shanying Lin; Ping Zhang; Honghua Xu (Ocean Engineering, 2023)

Experimental investigation and one-way coupled fluid-structure interaction analysis of gas-liquid two-phase flow conveyed by a subsea rigid M-shaped jumper - Guangzhao Li; Wenhua Li; Fenghui Han; Shanying Lin; Xingkun Zhou (Ocean Engineering, 2023)

Experimental evaluation of dimension-stable synthetic fibre rope under investigation of spooling test on the multilayer winch drum - Haoran Ye; Wenhua Li; Hongxin Zhang; Shanying Lin; Dinghua Zhang; Yangyuan Ge; Zehua Li (Ocean Engineering, 2023)

Temperature and Humidity Effects on the Dynamic Stiffness of a Polyester Mooring Rope - Wenhua Li; Xiongyan Liu; Gen Li; Shanying Lin; Hangyu Li; Yangyuan Ge (Journal of Marine Science and Engineering, 2023)
In this paper, the nonlinear stiffness of a polyester rope under dynamic loads at different temperatures was experimentally investigated. The effects and evolution of the average load, load period and load amplitude on dynamic stiffness were studied. The experimental results show that the dynamic stiffness at 30 °C was greater than that at 20 °C and 40 °C. This is because the dynamic stiffness reduced as the temperature and humidity increased, while in the closed thermostat, humidity decreased with an increase in temperature. In response to this phenomenon, a new set of empirical equations was proposed to consider temperature, humidity, and dynamic load based on the existing empirical formulas, by combining the experimental results. A set of experiments was conducted at 25 °C to verify the accuracy and applicability of the formula. The experimental results and the predicted results are in good agreement.

Effects and mechanisms of anionic and nonionic surfactants on biochar removal of chromium - Qiwei Chai; Li Lu; Yan Lin; Xueqin Ji; Chunping Yang; Shanying He; Dong Zhang (Environmental Science and Pollution Research, 2018)